The nutritive value of condensed wheat distillers solubles for cattle. (16th May 2016) - De Boever, J. L.; Blok, M. C.; Millet, S.; Vanacker, J.; De Campeneere, S.
Abstract : The chemical composition and the energy and protein value of five batches of condensed distillers solubles (CDS) originating from wheat were determined. The net energy for lactation (NEL) was derived from digestion coefficients obtained with sheep. The true protein digested in the small intestine (DVE) and the rumen degradable protein balance (OEB) were based on the rumen degradation rate ( kd D ), the rumen undegradable fraction ( U ) and intestinal digestibility of undegraded protein (%DVBE) predicted by regression equations derived from a data set of 28 protein feeds with kd D, U and %DVBE determined in situ . The CDS is a by-product with a high, but very variable CP content (238 to 495 g/kg DM). The CP contained on average 81% amino acids, with glutamine as main component (on average 21.8% of CP) and a relatively good lysine proportion (3.0%). Further, CDS contains quite a lot of crude fat (mean±SD: 71±14 g/kg DM), glycerol (95±52 g/kg DM) and sugars (123±24 g/kg DM) resulting in a high organic matter digestibility (88.6±3.0%) and high NEL content (8.3±0.4 MJ/kg DM). The protein value showed a large variation, with DVE ranging from 122 to 244 g/kg DM and OEB from 50 to 204 g/kg DM. Wheat CDS is a rich source of minerals and trace elements with exception of calcium.